2007
DOI: 10.1111/j.1095-8649.2007.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet, growth and recruitment of wild zebrafish in Bangladesh

Abstract: The diet of zebrafish Danio rerio in Bangladesh consisted primarily of zooplankton and insects. Zebrafish was an annual species, with the main period of reproduction commencing just before the onset of the monsoon season. Growth rates varied with age and season, with the period of most rapid growth in early life during the monsoon months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 10 publications
2
89
0
3
Order By: Relevance
“…Zebrafish is considered to have a wide thermal tolerance zone (72) and lives in the 16.5 to 38.6°C range of temperature in the wild (73,74). Interestingly, the elevated temperature used in this study, 36°C, falls within the above range.…”
Section: Discussionmentioning
confidence: 87%
“…Zebrafish is considered to have a wide thermal tolerance zone (72) and lives in the 16.5 to 38.6°C range of temperature in the wild (73,74). Interestingly, the elevated temperature used in this study, 36°C, falls within the above range.…”
Section: Discussionmentioning
confidence: 87%
“…Apparently wild zebrafish are generalists, consuming a wide variety of benthic and planktonic crustaceans, worms and insect larvae (Dutta 1993). McClure et al (2006) and Spence et al (2007) analyzed gut contents of sampled zebrafish in natural habits and found that insects, mostly of terrestrial origin, were the predominant prey; the diet also included a small percentage of plankton, whose main components identified were zooplankton and insects (58.6%), invertebrate eggs and arachnids (2.5%), phytoplankton (5.9%) and other unidentified components (33%). Zebrafish in captivity may be fed with live prey such as brine shrimp (Artemia sp.…”
Section: Diet Of the Zebrafishmentioning
confidence: 99%
“…Previous research has documented that zebrafish consume bacteria in the wild. 38 It would stand to reason then that microflora growing on feed and other organic waste would serve as supplemental nutrition for laboratory-reared zebrafish. The system used in this study incorporated self-cleaning tanks containing baffles at the back end of the tank for facilitating solids removal.…”
Section: Fig 2 Gonadosomatic Index (Gsi) Of Zebrafish Males (A)mentioning
confidence: 99%